Improving the Ability of MTs Mathematics Teachers Using Mathematics Learning Media Through the Training of "Kelasmen" Model in Target Madrasah in the Temanggung Regency - Anik Yuliani (Indonesian Journal of Mathematics Education, 2020)
The purpose of this research was to improve the ability of MTs mathematics teachers in the Temanggung regency to use mathematics learning media through the training of the Kelasmen model. This was supervisory action research. The research period was three months from mid of February 2019 to mid of April 2019. This research was conducted in three cycles on mathematics teachers in the Pringsurat, Tembarak, Selopampang, Kaloran, and Temanggung subdistrict in eleven targets MTs in Temanggung regency. The stages undertaken by the researcher in this study are (1) the preliminary initial reflection stage, (2) the planning stage, (3) the implementation phase of the action, (4) the observation phase, and (5) the reflection phase. After being given training through the Kelasmen model on the use of mathematics learning media, the ability of mathematics teachers in eleven MTs in Temanggung regency experienced an improvement from 53.33% in cycle I to 66.67% in cycle II and  86.67% in cycle III. Therefore, it could be concluded that the training of the Kelasmen model could improve the ability of MTs mathematics teachers in the Temanggung regency to use mathematics learning media. Thus the hypothesis of the proposed action was declared successful and accepted.